2018
DOI: 10.1037/dev0000448
|View full text |Cite
|
Sign up to set email alerts
|

Spatial but not temporal numerosity thresholds correlate with formal math skills in children.

Abstract: Humans and other animals are able to make rough estimations of quantities using what has been termed the approximate number system (ANS). Much evidence suggests that sensitivity to numerosity correlates with symbolic math capacity, leading to the suggestion that the ANS may serve as a start-up tool to develop symbolic math. Many experiments have demonstrated that numerosity perception transcends the sensory modality of stimuli and their presentation format (sequential or simultaneous), but it remains an open q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 86 publications
6
60
1
Order By: Relevance
“…That Magnitude relates to number acuity is in line with previous studies with both typical children and children with low math achievement (Anobile et al, 2013;Piazza et al, 2010). Interestingly, despite the ability to perceive numerosity is largely generalized, integrating information across space (dots arrays), time (flashes and sounds streams) and even actions (finger tapping), children math skills only correlates with estimation of spatial numerosity (Anobile, Arrighi, Togoli, & Burr, 2016;Anobile et al, 2017;Arrighi, Togoli, & Burr, 2014). The parietal cortex (mainly intraparietal sulcus, IPS) is a good candidate to represent the brain area mediating this connection (Ansari & Dhital, 2006;Castaldi, Aagten-Murphy, Tosetti, Burr, & Morrone, 2016;Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…That Magnitude relates to number acuity is in line with previous studies with both typical children and children with low math achievement (Anobile et al, 2013;Piazza et al, 2010). Interestingly, despite the ability to perceive numerosity is largely generalized, integrating information across space (dots arrays), time (flashes and sounds streams) and even actions (finger tapping), children math skills only correlates with estimation of spatial numerosity (Anobile, Arrighi, Togoli, & Burr, 2016;Anobile et al, 2017;Arrighi, Togoli, & Burr, 2014). The parietal cortex (mainly intraparietal sulcus, IPS) is a good candidate to represent the brain area mediating this connection (Ansari & Dhital, 2006;Castaldi, Aagten-Murphy, Tosetti, Burr, & Morrone, 2016;Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, some studies demonstrated that mathematical abilities do not correlate with specific computations: size and density sensitivity do not correlate with math, in contrast to visual numerosity (Anobile et al, 2016(Anobile et al, , 2018. Similarly, average size (Castaldi et al, 2018), line length (Cappelletti et al, 2014;De Visscher et al, 2017) and area (Iuculano et al, 2008) are not impaired by dyscalculia, a learning deficit affecting number processing.…”
Section: Discussionmentioning
confidence: 99%
“…One widely influential theory of numerical cognition proposed as the very first building block of mathematical knowledge the preverbal capacity to quickly determine the number of items in an image, based on the so called 'number sense' (Dehaene, 1997), that humans share with other animals since very early in life (Cantlon, 2012;de Hevia et al, 2017). During development, non-symbolic quantities are thought to be associated with symbolic numerals and the ability to fluently manipulate numerical magnitudes in these various formats, for example in the context of a numerical comparison task, has been shown to predict more complex arithmetical abilities (Anobile et al, 2016(Anobile et al, , 2018Halberda et al, 2008;Libertus et al, 2011Libertus et al, , 2013Bugden et al, 2012;Holloway and Ansari, 2009;Sasanguie et al, 2012;Price and Fuchs, 2016;Chen and Li, 2014;Fazio et al, 2014;Schneider et al, 2017;Starr et al, 2017).…”
Section: Introductionmentioning
confidence: 99%